PENGEMBANGAN ALAT PRAGA RAUSE SAMPAH UNTUK MENINGKATKAN PEMAHAMAN KONSEP LINGKUNGAN SISWA KELAS V SD - Siregar, Yulisa Dwi; Zainuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop simple teaching aids based on waste reuse to increase understanding of environmental concepts for fifth grade students at SD Negeri 116897 Hapoltakan Nauli. The method used in this research is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects were fifth grade elementary school students. The research results showed that the teaching aids developed were valid with an average expert validation score of 88.5% (very valid). The use of waste reuse-based teaching aids is effective in increasing students' understanding, as evidenced by the pre-test results with an average of 60.3 increasing to 82.7 in the post-test. Student responses to the teaching aids were also very positive with a practicality level of 89.2%. In conclusion, waste reuse-based teaching aids can be an innovative solution in increasing understanding of environmental concepts in elementary school students.